PENGARUH DOSIS PUPUK KANDANG AYAM DAN PUPUK ORGANIK CAIR (POC) URIN KELINCI TERHADAP PERTUMBUHAN DAN HASIL KACANG TUNGGAK (Vigna unguiculata L.): Kacang Tunggak,Pupuk Organik, Pupuk Kandang Ayam, POC urin kelinci - Mauna, Duta; Ratna Nurhayati, Dewi; Nikmatu Sholihah, Efi (innofarm, 2025)
This research is entitled The Effect of Doses of Chicken Manure and Rabbit Urine Liquid Organic Fertiliser on the Growth and Yield of Cowpea Plants (Vigna unguiculata L.). The purpose of this study was to determine the effect of a combination of chicken manure and rabbit urine liquid organic fertiliser on the growth and yield of cowpea plants. This research was conducted in Tambakwetan Rt 03 Rw 07, Tambakmerang, Girimarto, Wonogiri, Central Java. This research design used a 2-factorial randomised complete blok design (RAKL). The first factor of chicken manure dose (A) consisted of 3 levels A0 (0 tonnes/ha), A1 (20 tonnes/ha), A2 (40 tonnes/ha). The second factor of rabbit urine POC (K) consisted of 3 levels K0 (0 ml/ha), K1 (40 ml/ha), K2 (80 ml/ha). The parameters observed were plant height, number of leaves, wet stover weight, dry stover weight, number of pods, pod weight, wet seed weight, dry seed weight. The results of the study are the Dosage Treatment of Chicken Manure gives results that are not significantly different from all observation parameters. The treatment of Rabbit Urine POC gives results that are not significantly different from all observation parameters. The combination of treatments between chicken manure doses and rabbit urine POC gave significantly different results on the observation parameter of plant height A0K0 (104.83 cm). But not significantly different from the parameters of the number of leaves, the weight of wet stalks, the weight of dry stalks, the number of pods, pod weight, wet seed weight, seed weight. Keywords: Cowpea,Organic Fertiliser,Chicken Manure, Rabbit urine POC